The application of psychological methods in evaluation of thought in patients with schizophrenia - Gailienė, D. (Psichologija, 1982)
This article presents the results of experimental-psychological research of thought evaluation in patients with schizophrenia: 89% of the tasks could detect thought disorders in 86% of subjects. The diagnostic value of the method varies. The most valuable appeared to be the method of object exclusion. The necessity to use the compendium of methods in evaluation of thought in patients with schizophrenia is emphasized.
Keywords: schizophrenia; thought; schizophrenia diagnostics; thinking